Visual perception of phrasing in a tai chi routine by using different music accompaniment - Loo, Fung Chiat; Loo, Fung Ying (Elsevier BV, 2015)
This study looks into the visual perception of phrasing in a Tai Chi routine as affected by a change of music. The research aimed to investigate whether the quality of phrasing between music and movement is improved with a more congruent accompaniment. Sixty respondents, undergraduate music majors from two universities in Malaysia, were invited to participate in this study. They were asked to evaluate the phrasing between music and movement in videos of the same Tai Chi routine but with two different music accompaniments. It was found that there is a significant difference in the evaluation, and that the video with music composed to provide a better congruence in phrasing received a higher rating.